Azacitidine in Lower‐Risk Myelodysplastic Syndromes: A Meta‐Analysis of Data from Prospective Studies. (8th November 2017) - Komrokji, Rami; Swern, Arlene S.; Grinblatt, David; Lyons, Roger M.; Tobiasson, Magnus; Silverman, Lewis R.; Sayar, Hamid; Vij, Ravi; Fliss, Albert; Tu, Nora; Sugrue, Mary M.
Abstract : Background: After erythropoiesis‐stimulating agent (ESA) failure, lenalidomide and hypomethylating agents are the only remaining treatment options for most patients with lower‐risk myelodysplastic syndromes (LR‐MDS). Optimal choice of these agents as front‐line therapy in non‐del(5q) LR‐MDS is unclear. Because azacitidine clinical data mainly describe experience in higher‐risk MDS, we performed a meta‐analysis of patient‐level data to evaluate azacitidine in patients with red blood cell (RBC) transfusion‐dependent LR‐MDS. Materials and Methods: We searched English‐language articles for prospective phase II and III azacitidine clinical trials and patient registries published between 2000 and 2015, and Embase abstracts from 2015 conferences. Patient‐level data from identified relevant studies were provided by investigators. Meta‐analyses followed Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. Efficacy endpoints were RBC transfusion independence (TI) and Clinical Benefit (RBC‐TI, erythroid response, and complete or partial remission, per International Working Group 2006 criteria for MDS). Results: Data for 233 patients from 6 clinical studies and 1 registry study met criteria for inclusion in analyses. Overall, 90.3% of patients had non‐del(5q) LR‐MDS. Pooled estimates from random‐effects models of RBC‐TI and Clinical Benefit were 38.9% and 81.1%, respectively; for the ESA‐refractory subgroup, they were 40.5% and 77.3%; and for patients with isolated anemia, they were 41.9% and 82.5%. In multivariate analyses, planned use of ≥6 azacitidine treatment cycles was significantly predictive of response. Conclusion: Azacitidine effects in these patients, most with non‐del(5q) LR‐MDS, were promising and generally similar to those reported for lenalidomide in similar patients. The choice of initial therapy is important because most patients eventually stop responding to front‐line therapy and alternatives are limited. Implications for Practice: Lower‐risk myelodysplastic syndromes (LR‐MDS) are primarily characterized by anemia. After erythropoiesis‐stimulating agent (ESA) failure, lenalidomide and hypomethylating agents are the only remaining treatment options for most patients. This meta‐analysis of 233 azacitidine‐treated red blood cell (RBC) transfusion‐dependent patients with LR‐MDS (92.3% non‐del[5q]) from 7 studies showed 38.9% became RBC transfusion‐independent. There is no clear guidance regarding the optimal choice of lenalidomide or hypomethylating agents for patients with non‐del(5q) LR‐MDS following ESA failure. Clinical presentation (e.g., number of cytopenias) and potential outcomes after hypomethylating agent failure are factors to consider when making initial treatment decisions for LR‐MDS patients. Abstract : To assess the effectiveness of first‐line azacitidine in red blood cell transfusion‐dependent lowerrisk myelodysplastic syndrome, a prospective meta‐analysis of azacitidine treatment was performed in this population.